Judicial Sequestration in Al-Ghazali's Ethical Framework: An Islamic Perspective on Judicial Reform in Indonesia - Khoiriyah Khoiriyah; Fauzan Muzakki (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Judicial independence is a foundational principle in ensuring the rule of law and public trust in the judiciary. In Indonesia, this principle faces serious challenges due to recurrent judicial corruption, as revealed by multiple bribery sting operations involving judges. This article examines the concept of judicial sequestration—the isolation of judges from external influences during adjudication—as a potential safeguard for judicial impartiality. Drawing upon Al-Ghazali’s ethical framework, the study argues that effective judicial reform must integrate moral virtues such as piety, independence, and resistance to political and personal pressures. The analysis employs a normative-legal and comparative approach, juxtaposing Al-Ghazali’s judicial ethics with sequestration practices in common law systems. The findings suggest that embedding Islamic ethical values within institutional reform frameworks can enhance judicial integrity and accountability. In particular, a culturally contextualized model of judicial sequestration may serve as a viable mechanism for strengthening judicial independence in Indonesia. This study contributes to ongoing discourse on legal reform by offering a synthesis of classical Islamic thought and modern judicial ethics.